Fulminant Type 1 Diabetes as a Model of Nature to Explore the Role of C-Peptide. (15th April 2008) - Murase-Mishiba, Yuko; Imagawa, A.; Hanafusa, Toshiaki
Abstract : Patients with fulminant type 1 diabetes almost completely lack C-peptide even soon after the onset of the disease, and the deficiency continues for the rest of their life. Thus, fulminant type 1 diabetes could serve as a good model of nature to explore the physiological role of C-peptide. For example, patients with fulminant type 1 diabetes have diabetic chronic complications more frequently than those with classical autoimmune type 1 diabetes 5 years after the onset of diabetes, and the higher prevalence could be partly attributable to the complete lack of C-peptide in fulminant type 1 diabetes.